2004
DOI: 10.1093/humrep/deh010
|View full text |Cite
|
Sign up to set email alerts
|

Serum and adipocyte resistin in polycystic ovary syndrome with insulin resistance

Abstract: These results suggest that overexpression of the resistin gene in adipocytes may be a local determinant factor in the pathogenesis of PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
55
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(63 citation statements)
references
References 36 publications
4
55
0
3
Order By: Relevance
“…However, serum resistin levels were found to be higher in obese and non-obese Chinese PCOS groups in comparison with controls, suggesting that resistin may be implicated in the regulation of insulin resistance in this PCOS ethnic group (Wang et al 2010). In terms of gene expression, Seow et al (2004) reported data on resistin mRNA expression in isolated adipocytes from OM adipose tissue of Taiwanese women with PCOS and age-and weightmatched non-PCOS. An overexpression of the resistin gene was found in adipocytes from PCOS, suggesting that resistin may play a role in the local pathogenesis of PCOS.…”
Section: Resistinmentioning
confidence: 99%
“…However, serum resistin levels were found to be higher in obese and non-obese Chinese PCOS groups in comparison with controls, suggesting that resistin may be implicated in the regulation of insulin resistance in this PCOS ethnic group (Wang et al 2010). In terms of gene expression, Seow et al (2004) reported data on resistin mRNA expression in isolated adipocytes from OM adipose tissue of Taiwanese women with PCOS and age-and weightmatched non-PCOS. An overexpression of the resistin gene was found in adipocytes from PCOS, suggesting that resistin may play a role in the local pathogenesis of PCOS.…”
Section: Resistinmentioning
confidence: 99%
“…Indeed, due to its low mRNA expression level in human adipose tissue, it was initially concluded that this molecule was unlikely to be an important factor linking human obesity to insulin resistance. [71][72][73] However, several recent studies reported that resistin serum levels are increased in obesity [74][75][76] or type 2 diabetes, 77,78 with significant correlations often being observed between resistin levels and the BMI, 75 basal glycemia, 77 insulin resistance, 75,79,80 C-reactive peptide, 78 and hepatic lipid content. 80 In keeping with these observations, as well as with the well-known association among central obesity, insulin resistance, and type 2 diabetes, resistin mRNA and protein expression were shown to be higher in human central adipose tissue depots compared with thigh and breast adipose tissue.…”
Section: Resistinmentioning
confidence: 99%
“…A significant correlation between resistin and BMI had also been demonstrated. Resistin mRNA levels in adipocytes were increased 2-fold in PCOS patients (Seow et al, 2004), suggesting that the resistin gene may be a local determining factor in the pathogenesis of PCOS. Our study aims: (1) to measure serum and follicular resistin, steroids hormone levels in women with PCOS; (2) to assess possible correlations of resistin to the hormonal and metabolic parameters; (3) to analyze the clinical outcomes of in vitro fertilization-embryo transfer (IVF-ET) in women with PCOS and tubal infertility.…”
Section: Introductionmentioning
confidence: 98%